Xi'an bei lin bai tu ji shang - Xi'an bei lin bo wu guan. (Xi'an : Shanxi lü you chu ban she, 1992)
Ben shu jie xuan le li dai you dai biao xing de bei shi 150 zhong.
Jing zhe zhuang.
In Chinese and English and Japanese.
Keywords: Calligraphy, Chinese; Inscriptions, Chinese -- China -- Xi'an Shi; Epitaphs -- China -- Xi'an Shi; Calligraphy, Chinese; Epitaphs; Inscriptions, Chinese; China -- Xi'an Shi